Evaluating the preoperative diagnostic value of 99m Tc‐MIBI/ 99m TcO 4 − dual‐isotope SPECT/CT fusion imaging and ultrasonography in suspected primary hyperparathyroidism - Yanmei Li; Danna Hou; Zhehao Lyu; Xingrong Lan; Ziyue Zhang; Yu Lu; Peng Fu; Huiqi Gao (Journal of Applied Clinical Medical Physics, 2026)
Abstract Background Primary hyperparathyroidism (PHPT) is a common endocrine disorder that often requires surgical intervention. Preoperative localization of parathyroid lesions is critical for successful surgery. This study compares the diagnostic value of 99m Tc‐MIBI/ 99m TcO 4 − dual‐isotope SPECT/CT fusion imaging and ultrasonography (US) in patients with suspected PHPT, and explores the correlation between lesion volume and preoperative serum biochemical markers. Objective This study aimed to assess the preoperative diagnostic performance of US and 99m Tc‐MIBI/ 99m TcO 4 − dual‐isotope SPECT/CT fusion imaging in PHPT and investigate the relationship between serum parameters and parathyroid adenoma volume. Methods A retrospective analysis was conducted on 75 patients with elevated parathyroid hormone (PTH) levels and suspected primary hyperparathyroidism between September 2023 and November 2024. All patients underwent 99m Tc‐MIBI/ 99m TcO 4 − dual‐isotope SPECT/CT fusion imaging and US. Using surgical histopathology as the gold standard, the sensitivity and positive predictive value (PPV) of both imaging modalities in detecting parathyroid lesions were calculated. Additionally, a preliminary analysis was performed to assess the relationship between lesion volume and preoperative serum biochemical markers. Results Among the 75 patients, 68 were confirmed as PHPT cases, with a total of 74 parathyroid lesions identified. As per patient‐based analysis, the diagnostic sensitivities of 99m Tc‐MIBI/ 99m TcO 4 − dual‐isotope SPECT/CT fusion imaging and US were 94.12% (64/68) and 86.76% (59/68), respectively, with SPECT/CT demonstrating superior sensitivity. Per lesion‐based analysis revealed that SPECT/CT significantly outperformed US in both sensitivity (97.01% vs. 79.10%, P < 0.001) and PPV (85.87% vs. 80.72%, P = 0.006). Subgroup analysis showed that in group of the classical primary hyperparathyroidism (CPHPT), SPECT/CT exhibited higher sensitivity (96.22% vs. 84.91%, P < 0.001) and PPV (94.64% vs. 82.45%, P = 0.039) compared to US, whereas no significant difference was observed in group of the normocalcemic primary hyperparathyroidism (NPHPT). Additionally, in group of the CPHPT, moderate correlations were found between lesion volume and corrected serum calcium (Corr Ca) ( r = 0.435, P = 0.003) as well as PTH levels ( r = 0.303, P = 0.045). Conclusion The dual‐isotope SPECT/CT fusion imaging has high diagnostic efficacy for PHPT, which can accurately locate lesions and provide reliable preoperative guidance for surgery. For patients with normal blood calcium but clinical symptoms of PHPT, combining this examination with ultrasound may offer complementary diagnostic value, although this finding requires validation in larger prospective studies. The degree of elevation in serum calcium and PTH levels can predict the volume and metabolic activity of parathyroid adenomas, and relevant biochemical indicators can guide the clinical screening of patients suitable for this examination.